Abu l-Hassan Ali al-Nadawi's approach to renewal and reform (Tajdid wa Islah) - Ali, Mohammed Farid (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2014)
Our remarks are based on two works by Abu l-Hasan Ali Nadawi (d. 1999), a well known scholar of Arabic language, Islamic culture and da’wah. The first work is Tarikh-i-Da’wat wa ‘Azimat, originally written in Urdu then rendered into Arabic as “Rijal al-Fikr wa al-Da’wah fi al-Islam” and into English as “Saviours of the Islamic Spirit”. The second work is Islam and the World: Rise and Decline of Muslims and its Effect on Mankind. We shall briefly present Nadawi’s theory of renewal, his approach to understanding the contributions of Islamic scholars, leaders, and Sufi shaykhs in this field, as well as his identification of the causes which have brought about the decline of Muslim civilisation.